Public Relations / Strategies and Tactics - Agee Warren K.; Ault Phillip H.; Wilcox Dennis L (Harper Collins College Publishers, 2000)
Role, What is Public Relations, The Individual in Public Relations, Ethics and Professionalism, Process, Planning the Action, Evaluation, Strategy, Public Opinion and Persuasion, Public Relations and the Law, Application, Corporations, International Public Relations, Membership Organizations, Education, Entertainment and Sports and Travel, Tactics, Written Tactics, Spoken Tactics, Visual Tactics, Bibliography, Index.
Role, What is Public Relations, The Individual in Public Relations, Ethics and Professionalism, Process, Planning the Action, Evaluation, Strategy, Public Opinion and Persuasion, Public Relations and the Law, Application, Corporations, International Public Relations, Membership Organizations, Education, Entertainment and Sports and Travel, Tactics, Written Tactics, Spoken Tactics, Visual Tactics, Bibliography, Index.